2023
DOI: 10.26599/jac.2023.9220749
|View full text |Cite
|
Sign up to set email alerts
|

Fast ion-conducting high-entropy garnet solid-state electrolytes with excellent air stability

Abstract: The garnet-type electrolyte is one of the most promising solid-state electrolytes due to its high ionic conductivity and wide electrochemical window. However, such electrolytes generate Li2CO3 in the air, leading to an increase in impedance, which greatly limits their practical application.In turn, high-entropy ceramics can improve phase stability due to the high entropy effect. Herein, the high-entropy garnet (HEG) Li6.2La3(Zr0.2Hf0.2Ti0.2Nb0.2Ta0.2)2O12 (LL(ZrHfTiNbTa)O) solid-state J u s t A c c e p t e d h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The electronic conductivity of LLZTO was shortened from 1.4 × 10 −8 to 1.8 × 10 −10 S cm −1 after electron-blocking layer deposition. Figure 5b and Table S1 show the electronic conductivity comparison chart of our work with other literature reports 23 , 40 , 42 – 49 , which is the lowest value among reported publications.
Fig.
…”
Section: Resultsmentioning
confidence: 50%
“…The electronic conductivity of LLZTO was shortened from 1.4 × 10 −8 to 1.8 × 10 −10 S cm −1 after electron-blocking layer deposition. Figure 5b and Table S1 show the electronic conductivity comparison chart of our work with other literature reports 23 , 40 , 42 – 49 , which is the lowest value among reported publications.
Fig.
…”
Section: Resultsmentioning
confidence: 50%
“…The electronic conductivity of LLZTO was shortened from 1.4×10 − 8 S cm − 1 to 1.8×10 − 10 S cm − 1 after KF buffer layer deposition. Figure 5b and Table S1 showed the electronic conductivity comparation chart of our work with other literature reports 23,33,[35][36][37][38][39][40][41][42] , which is the lowest value among reported publications.…”
Section: Resultsmentioning
confidence: 55%
“…The Ti doping improves the density, while the Hf doping prevents the Li + /H + exchange to enhance the air stability. The synergistic effect of multiple elements increases both air stability and ionic conductivity of high-entropy garnet [95]. Jung et al revealed that the high-entropy effects (e.g.…”
Section: Mechanism For High-entropy Electrolytesmentioning
confidence: 99%
“…In the LL(ZrHfTiNbTa)O electrolyte, Hf inhibits the Li + /H + from exchange, improving the air stability. Nb and Ta have the capability to enhance the ionic conductivity [95]. Additionally, Ti is able to prevent the Li dendrites [114].…”
Section: The Impacts Of Individual Components On the Electrochemical ...mentioning
confidence: 99%